The rule of academic commercialization: The Bayh Dole Act in Iran and USA - Khosravi, Saber; Ahmadi, Mahnaz; Barazandeh, Mahtab (Journal of Entrepreneurship, Business and Economics; Vol 2 No 2 (2014), 2014)
Purpose- Just before the approval of the Bayh dole Act, universities and colleges in the United States of America were used to be associations with the main aim focused on research and education and they could not imagine taking other missions. The approval of this act gave universities the right to submit and take advantage of their research results and academic achievements as intellectual properties which were done by governmental budget. Still over fifty years the Bayh dole Act is considered as the most inspiring act and significant factor in salient development of innovation and its consequent national productivity in the 1990s economy of America. With the encouraging economic and financial outcomes, many other countries like Iran got enthusiastic to authorize and implement the same act. Although Islamic Republic of Iran with developing economy has approved similar academic commercialization rules, they were not successful in practice. Consequently they could not result to similar effects of the Bayh dole Act such as the mutation in development of academic innovation or the commercialization of knowledge base products in universities and, apparently they could not even increase the transfer technology offices (TTO) or the number of university patents and products either. Design/methodology/approach- This article first introduces the background and the contexts of the Bayh dole passage in America and then explains the Act‟s main outcomes in America‟s innovation and academic commercialization system. Also it takes a brief look at the similar rules and regulations in other countries including Singapore, China and India. Findings- Moreover, this article contains the comparative study of these regulations and related acts in other countries, especially in America, and their similarities and differences. Finally, by interviewing the Iranian inventers and experts, the defect of internal acts, factors and reasons of their disappointed implementation are illustrated. Research paper Reference to this paper should be made as follows: Khosravi, S., Ahmadi, M., Barazandeh, M. (2014). “The rule of academic commercialization: The Bayh Dole Act in Iran and USA”, Journal of Entrepreneurship, Business and Economics, Vol. 2, No. 2, pp. 10–25.